MENINGKATKAN KEMAMPUAN TOILET TRAINING MELALUI ANALISIS TUGAS PADA ANAK TUNAGRAHITA SEDANG - Reni AA Panjaitan, Irdamurni, Kasiyati (Universitas Negeri Padang, 2013)
The research was motivated by problems that occur in SLB N 1 Padang that mentally retarded child X third graders were aged 17 years old who have difficulties in terms of self help especially toilet training in performing urination. This aim of this study was to improve the ability of toilet training for mentally retarded child going through a task analysis. The research methodology is Single Subject Research (SSR) a research design is A-B, which the design of study was comparing the ability of toilet training mentally retarded child X on the baseline and the intervention condition. The results were analyzed include the number of observations in the baseline condition as much as eight times and the intervention condition as many as fifty-two sessions per week. Results of this study aimed at the data analysis in conditions and the data analysis between conditions indicate a change in the ability of toilet training X to better direction, which is proven from the data obtained during the baseline condition, was only 37, 5% whereas the data obtained during the intervention conditions at fifty to fifty-two sessions the children's ability to toilet training was 100%.